2023
DOI: 10.1177/00302228231162730
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Validation of the Persian Traumatic Grief Inventory-Self Report Plus (TGI-SR+) to Assess Prolonged Grief Severity

Abstract: The Traumatic Grief Inventory-Self Report Plus (TGI-SR+) is a self-report measure to assess Prolonged Grief Disorder (PGD) in terms of ICD-11 and DSM-5-TR. Till now this measure has shown to yield good psychometric properties in Dutch and French speaking bereaved people. This study aimed to evaluate the psychometric properties of the Persian TGI-SR+. 461 individuals (280 women) fully completed the scales. The participants were recruited using convenience sampling. The Confirmatory factor analysis and concurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Our second main finding was that, in the whole sample as well as the recently (<6 months) and more remotely bereaved (≥6 months) subsamples considered separately, PGD symptoms formed a unitary factor. This is consistent with prior research showing that PGD symptoms as defined in ICD-11 are best described as forming one dimension (Ashouri & Yousefi, 2023;Boelen & Lenferink, 2020;Kokou-Kpolou et al, 2022;Lenferink et al, 2022Lenferink et al, , 2024. Notably, some other studies have found these symptoms to represent two distinguishable dimensions of separation distress and accompanying symptoms (e.g., Hyland et al, 2024;O'Conner et al, 2023); however, in most of the studies examining the dimensionality, both the one-and two-dimensional models evidenced acceptable fit.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our second main finding was that, in the whole sample as well as the recently (<6 months) and more remotely bereaved (≥6 months) subsamples considered separately, PGD symptoms formed a unitary factor. This is consistent with prior research showing that PGD symptoms as defined in ICD-11 are best described as forming one dimension (Ashouri & Yousefi, 2023;Boelen & Lenferink, 2020;Kokou-Kpolou et al, 2022;Lenferink et al, 2022Lenferink et al, , 2024. Notably, some other studies have found these symptoms to represent two distinguishable dimensions of separation distress and accompanying symptoms (e.g., Hyland et al, 2024;O'Conner et al, 2023); however, in most of the studies examining the dimensionality, both the one-and two-dimensional models evidenced acceptable fit.…”
Section: Discussionsupporting
confidence: 87%
“…Increased knowledge about these issues could inform bereavement research and help to shape health care policies to improve bereavement care (cf. Ashouri & Yousefi, 2023;Hyland et al, 2024;Killikelly et al, 2020;Shevlin et al, 2023). The current study examined prevalence rates of ICD-11based PGD associated with a loss within the previous year, in a representative sample of the adult Slovakian population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations